Efektivitas Kebijakan Lima Hari Kerja pada Bidang Pelayanan Publik di Kantor Desa Penyamun Kecamatan Pemali Kabupaten Bangka - Resti Resti; Agus Sofyan; Sudarmawan Sudarmawan (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effectiveness of the five-day workday policy on public services at the Penyamun Village Office, Pemali District, Bangka Regency. The study used a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the five-day workday policy has been implemented in accordance with the Bangka Regent's Circular Letter of 2024 and has been able to maintain the continuity of public services by adjusting working days and hours. Village officials have been able to adapt to the new work system, although there are still disciplinary challenges and differences in public satisfaction levels. The five-day workday policy is considered effective and has had a positive impact on public services at the Penyamun Village Office. This study implies that the village government needs to improve apparatus discipline and evaluate the five-day workday policy to optimize public services.